Democratization of the economic government on the basis of societal-state-private partnership as means of opposition to take-over of enterprise - O. V. Smirnov (Известия высших учебных заведений: Геология и разведка)
The urgent nessesity of the democratization of the economic goverment is detected and justified for the mineral enterprises on the basis of strategic integrative interaction of stake-holders to make consistent decisions, preventing unfriendly take-over and raiding of economics objects. The complex of contr-raiding procedures has been characterized on the basis of successful Russian and world, i.d. Canadian, experience.